“Isso é algo que não era para ter acontecido”: o desastre-crime no rio doce em povoação/ES a partir da perspectiva das crianças - Gomes, Pedro Alves (2021)
The work proposes a different approach to the analysis of the disaster-crime in Doce river: from the perspective of children. It seeks to understand the effects and changes in daily life and the landscape, with the interlocutors of children from the district of Povoação / ES, a community affected by the implications of the arrival of the tailings mud from Samarco's mining activities in November 2015. From the children's perspective, the objective is to observe the changes in the community, resulting from the effects caused by the rupture of the dam, based on the ideas of landscape and daily life. The theoretical approach of the study privileges contributions from the field of child anthropology, sociological analyzes about childhood and playing practices, in addition to studies on the landscape. To this end, it is characterized as an exploratory work that uses participant observation, as well as other tools such as, for example, collection and analysis of children's drawings and focus groups. The data collected and observed here demonstrate the children's perception of the complexity and dimension of the dam breach for different areas of community life.